Comparative Study Of The Inductances Of An Induction Motor With Rotor Eccentricities - F. Rodriguez, Elkin; Andrés Santisteban, José; Carlos Ferreira, Antônio (Eletrônica de Potência, 2010)
In this work, the inductances of an induction motor, which rotor may be misaligned, are evaluated. Two types of analysis are performed: Analytical Method (AM) and Finite Element Method (FEM). For radial displacements, both methods show equivalent results but to evaluate inductances as a function of angular displacements, only with FEM was possible to get results as with AM it would be necessary intricate functions. The inductances obtained with FEM were included in simulations of a bearingless induction motor with split windings. This approach shows a good agreement with experimental results.